2016
DOI: 10.1111/joic.12277
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin‐Induced Platelet‐Fibrin Clot Strength Identified by Thrombelastography

Abstract: Patients with ISR identified at the time of cardiac catheterization have a prothrombotic phenotype indicated by high TIP-FCS, a novel marker. Studies to confirm the prognostic utility of high TIP-FCS for the development of ISR are ongoing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…preexisting hypercoagulable state. As noted by our group in a prior study, TIP-FCS >67 mm is associated with a thrombotic phenotype predictive of restenosis, which was observed in the case discussed [7]. An alternate explanation of the observed hypercoagulability could be from the high number of stents implanted as opposed to intrinsic patient-related factors.…”
supporting
confidence: 69%
“…preexisting hypercoagulable state. As noted by our group in a prior study, TIP-FCS >67 mm is associated with a thrombotic phenotype predictive of restenosis, which was observed in the case discussed [7]. An alternate explanation of the observed hypercoagulability could be from the high number of stents implanted as opposed to intrinsic patient-related factors.…”
supporting
confidence: 69%
“…Moreover, pharmacodynamic studies have ignored potential effects of vorapaxar on the viscoelastic and kinetic characteristics of platelet-fibrin clot formation, potential factors that may play a role in the development of adverse thrombotic events 18. In the Clopidogrel with Eptifibatide to Arrest the Reactivity of Platelets study (CLEAR Platelets II study), Gurbel et al 19 demonstrated a significant reduction in thrombin-induced platelet-fibrin clot strength with GPIIb/IIIa blockade with eptifibatide and a non-significant reduction using a direct thrombin inhibitor bivalirudin in patients undergoing elective coronary stenting.…”
mentioning
confidence: 99%
“…Considering the rapidly increasing number of cardiovascular patients 4 , restenosis has become a significant clinical concern. There are many pathological features of in-stent restenosis that limit the efficacy of percutaneous intervention 5 , including dysfunctional endothelial cells, proliferation and migration of vascular smooth muscle cells (VSMCs), and activation of inflammation 6 . As the principal component of vascular walls, VSMCs play crucial roles in both the physiological functions of blood vessels and the formation atherosclerotic lesions 7 .…”
mentioning
confidence: 99%